Teachers' Thoughts on Student Decision Making During Engineering Design Lessons - Helen Meyer (MDPI AG, 2018)
In this paper, I share the results of a study of teachers' ideas about student decision-making at entry into a professional development program to integrate engineering into their instruction. The framework for the Engineering Design Process (EDP) was based on a Challenge-Based Learning (CBL) model. The EDP embedded within the CBL model suggests teachers should provide opportunities for students to make decisions throughout the design process. The differentiation consolidation decision-making framework was used to understand the decision-making process. Study data was gathered from 16 teacher participants, interviewed and surveyed at entry into the program. The data were analyzed to understand the kinds of decision-making activities the teachers' identified as possible for students to make based on eleven engineering design scenarios and the teachers' current use of, and confidence in applying, lessons that engaged students in decision-making. The results indicated the teachers most frequently identified students that engaged in stage one decisions-making activities, i.e., problem identification and clarification. When the teachers discussed stage two and stage three decision-making activities, they most frequently discussed general problem solving or design process type activities with little differentiation of specific details of how the decision-making was to take place. In addition, in most cases teachers did not mention teaching or supporting student decision-making strategies.